Employing the rectangle strategy to alleviate poverty in Cambodia - Yah Awg Nik; Phyrum Vor (2013)
Cambodia is the second poorest country among the association of South East Asian Nations (UNDP, 2009). Its’ economy mainly depends on the agricultural production, garments, tourism and construction (Heng and Chanrith, 2010). The main cause of Poverty in Cambodia is characterized by low income, low consumption, few assets, poor nutritional status, starvation, low educational attainment, illiteracy and less capacity, less access to public services including school and health service. Poverty is also due to poor economic opportunities, high population growth, vulnerability and instability of political process (UNDP, 2009). This paper attempts to provide some insights of the Rectangle Strategy ( Reform Strategy 2004-2008) used by the government to alleviate poverty such as enhancement of agricultural sector, continued rehabilitation and construction of physical infrastructure and capacity building and human resource development. As for capacity building and human resource development the government has employed measures to enhance the quality of education, improve the health services and foster gender equity and implement population policy (Progress Report 2004 and IMF 2006). Consequently using this effective strategy has allowed the government to reduce the poverty rate among 1% per year and Cambodia’s economy grew at almost 10 percent per year between 1998 and 2008. Its’ GDP growth reached a four-year high of 7.1% (World Bank, 2013). The strategy has proven to be a great achievement of the reform in Cambodia in poverty eradication.